1994
DOI: 10.1177/0146167294203009
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and Deception in Children and Adults: Are Leaders the Best Misleaders?

Abstract: Relationships between dominance and nonverbal deception skill were investigated in preschool children (Study 1) and in under-graduate men and women (Study 2). Subjects were assessed for dominance during peer group interactions. Later, they encoded and decoded deceptive messages. Raters assessed the credibility of each subject's encoded message using nonverbal cues alone. Ability to encode credible, deceptive messages predicted dominance in preschool children and men but not women. Decoding deception accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 39 publications
(36 reference statements)
2
39
1
Order By: Relevance
“…The findings from this study are in keeping with past theory and results found within the social dominance and delinquency/conduct problems literatures (e.g., Keating & Heltman, 1994;Stouthamer-Loeber, 1986). The current research confirms past studies that have found deception, lying, and false statement behaviors in young children.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings from this study are in keeping with past theory and results found within the social dominance and delinquency/conduct problems literatures (e.g., Keating & Heltman, 1994;Stouthamer-Loeber, 1986). The current research confirms past studies that have found deception, lying, and false statement behaviors in young children.…”
Section: Discussionsupporting
confidence: 90%
“…Given past associations with deception and the conceptually related social dominance construct (Keating & Heltman, 1994) as well as with delinquency and physical aggression/conduct problems (Lahey et al, 1999;Loeber & Dishion, 1983;Stouthamer-Loeber, 1986), we predicted that both physical aggression and relational aggression would be associated with concurrent deception. Because both physical aggression and relational aggression have been found to have gender-specific associations with key developmental constructs, we tested for the moderation of these associations by gender.…”
Section: Deception and Aggression Subtypesmentioning
confidence: 96%
See 1 more Smart Citation
“…The acquisition of such social knowledge has been for several decades a focus of those studying cognitive and social development (e.g., Kohlberg, 1969;Piaget, 1965;Selman, 1976;Wellman, 1990). By late preschool or kindergarten, children have refined their abilities to coordinate and cooperate with peers (Cook & Stingle, 1974) as well as to deceive them (Keating & Heltman, 1994;LaFreniere, 1988).…”
Section: Developmental Implicationsmentioning
confidence: 99%
“…Posed smiles, in contrast, are not accompanied by feelings of happiness but are displayed by the sender "as if" they were happy. Such posed smiles may be exhibited for a variety of reasons -for example, in order to endear oneself to others, or to put them at ease (Hecht & LaFrance, 1998;Provine, 1997), as an attempt to manipulate or deceive others (Keating & Heltman, 1994) or in order to mask other emotional experiences (Ekman & Friesen, 1982). In social contexts it is important for perceivers not to conflate posed and genuine smiles into a general, amorphous form of positive facial expression and risk misperceiving happiness, and potentially the behavioral intentions of the smiler.…”
mentioning
confidence: 99%